Study the distribution and importance of Edible wild plants used in rural life In AL-Qardaha area - Latakia. - داود, ميساء; وفاء رجب , (Latakia University Journal -Biological Sciences Series, 2024)
The study was conducted in AL-Qardaha region on the Syrian coast, in the year 2022-2023, and it included 12 villages, belonged to 4 districts. The study aimed to inventory and document the wild edible plants in AL-Qardaha region, and to estimate the cultural importance of each plant (the importance of the role that the plant plays within a particular culture) using the Cultural Significance Index (CFSI). Data on plants were collected by conducting a questionnaire with 100 local residents. The number of wild edible species in the study area reached 80 plant species, belonged to 41 plant families. The Asteraceae family was the most abundant, represented by 8 species, followed by the Rosaceae family, represented by 7 species, then the Lamiaceae family, represented by 6 species, then both the Fabaceae family and the Apiaceae family, represented by 5 species for each family. The values of the Cultural Importance Index (CFSI) ranged between (1.08- 1382.4). Cichorium intybus, and Eryngium creticum, were species of very high cultural importance, they are vegetables that are eaten raw and cooked, such as Malva silvistris, and hyssop like Micromeria myrtifolia, and beverage like (Syriacus Thymus) as a flavouring, and the species of high cultural importance like Portuloca oleracea, Eruca sativa, which is a vegetable that is eaten raw and used with salads, and Urtica dioica and Inula viscosa among the plants that have medicinal benefits, and drinks like Matricaria chamomilla, and among the species that are eaten Crataegus azarolus. The highest percentage of known species for age groups was among individuals between 17-40 years of age, reached 85%, and the lowest percentage was among individuals between 6-16 years of age, and it did not exceed 19%, while the largest number for the presence of species, according to the opinions of the respondents, was in the village of Qalaat al-Mahalaba in the district of Joubat Burghal species reached 39 species, representing almost half of the known species, at a rate of 48.75%.